1988
DOI: 10.1152/jappl.1988.64.5.1837
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aminophylline on hypoxemia-induced ventilatory depression in the cat

Abstract: We designed experiments to evaluate changes in ventral medullary (VM) extracellular fluid (ECF) PCO2 and pH during hypoxemia-induced ventilatory depression (VD). Our aim was to investigate effects of aminophylline on VD and VM ECF acid-base variables. We used aminophylline because it inhibits adenosine, which is released within the brain during hypoxemia and could mediate VD. Experiments were performed in seven cats with acute bilateral denervation of carotid sinus nerves and vagi. Cats were anesthetized with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…The fact that the increase in respiratory frequency was smaller after both drugs can be explained as a direct consequence of the increase in respiratory cycle length. These observations are consistent with published reports that theophylline or aminophylline can ameliorate the secondary respiratory depression caused by hypoxia in several species, including neonate pig, adult cat and man (Millhorn, Eldridge, Kiley & Waldrop, 1984;Darnall, 1985;Easton & Anthionsen, 1988;Javaheri, Teppema & Evers, 1988). There is much evidence that methylxanthines stimulate respiration predominantly by an action within the central nervous system, probably within the brain stem, on neuronal adenosine receptors (Eldridge et al 1985).…”
Section: Effects Of Theophylline and 8-phenyltheophylline In Normoxiasupporting
confidence: 91%
“…The fact that the increase in respiratory frequency was smaller after both drugs can be explained as a direct consequence of the increase in respiratory cycle length. These observations are consistent with published reports that theophylline or aminophylline can ameliorate the secondary respiratory depression caused by hypoxia in several species, including neonate pig, adult cat and man (Millhorn, Eldridge, Kiley & Waldrop, 1984;Darnall, 1985;Easton & Anthionsen, 1988;Javaheri, Teppema & Evers, 1988). There is much evidence that methylxanthines stimulate respiration predominantly by an action within the central nervous system, probably within the brain stem, on neuronal adenosine receptors (Eldridge et al 1985).…”
Section: Effects Of Theophylline and 8-phenyltheophylline In Normoxiasupporting
confidence: 91%
“…An increase in tidal volume (without change in respiratory frequency) was thought to be due to the competition with adenosine at some of its central receptor sites [17]. In the present investigation, it seems likely that theophylline activated central respiratory receptors and reversed the hypoxic ventilatory depression [18]. This resulted in a more in-phase response of ventilation to altered blood gases with consecutive reduction of periodic breathing [19,20].…”
Section: Discussionmentioning
confidence: 56%
“…The decrease in ventilation of chemodenervated animals during hypoxia was attributed to an increase in cerebral blood flow and the consequent decrease in cerebrospinal fluid PCO 2 [11] and to the release of inhibitory neurotransmitters [12,13,16]. However, studies by Javaheri et al [17] on chemodenervated-vagotomized animals have shown that hypoxic ventilatory depression occurs both in the face of a rise or a fall in ventral medullary extracellular fluid PCO 2 and H + and is prevented by aminophylline.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, hypoxia influences the rate of synthesis or release of neurotransmitters and modulators [12,13], leading to accumulation of adenosine, dopamine and Á-aminobutyric acid in the brain [2,14,15]. Administration of long-acting analogues of adenosine, either systemically or directly into the third cerebral ventricle, decreases phrenic nerve activity in peripherally chemodenervated air breathing cats while theophylline, a specific antagonist of adenosine, prevents and reverses the decrease of phrenic activity [16] as reported by Javaheri et al [17]. These studies [16,17] clearly show the important role of adenosine in the central depressant effect of hypoxia in respiration in chemodenervated animals.…”
Section: Introductionmentioning
confidence: 99%